Barriers to developing a valid rodent model of Alzheimer's disease: from behavioral analysis to etiological mechanisms - Gidyk, Darryl C.; Deibel, Scott H.; Hong, Nancy S.; McDonald, Robert J. (Frontiers in Neuroscience, 2015)
Sporadic Alzheimer's disease is the most prevalent form of age-related dementia. As such, great effort has been put forth to investigate the etiology, progression, and underlying mechanisms of the disease. Countless studies have been conducted however the details of this disease remain largely unknown. Rodent models provide opportunities to investigate certain aspects of AD that cannot be ethically studied in humans. These animal models vary from study to study and have provided some insight, but no real advancements in the prevention or treatment of the disease. In this Hypothesis and Theory paper, we discuss what we perceive as barriers to impactful discovery in rodent AD research and we offer solutions for moving forward. Although no single model of AD is capable of providing the solution to the growing epidemic of the disease, we encourage a comprehensive approach that acknowledges the complex etiology of AD with the goal of enhancing the bidirectional translatability from bench to bedside and vice versa.